Leukocyte function-associated antigen 1 (LFA-1) and CD44 are signalling molecules for cytoskeleton-dependent morphological changes in activated T cells - KELLEHER, DERMOT P (Oxford University Press, 1995)
Signaling through the leukocyte function-associated antigen 1 (LFA-1) molecule has previously been shown to induce homotypic aggregation in T cells and to induce cytoskeletal changes in T lymphoma cells. In this study we describe the induction of a dendritic phenotype associated with cytoskeletal rearrangement in activated human peripheral blood T cells stimulated with monoclonal antibody SPV-L7 to LFA-1 alpha. Maximal expression of this phenotype required 72 h preactivation with phorbol myristate acetate and expression was abolished using the protein kinase C inhibitor staurosporine. Monoclonal antibody to CD18, the beta-chain of LFA-1, did not induce this phenotype. Monoclonal antibody MEM 83 to presumably a discrete epitope on LFA-1 alpha did not induce this phenotype but induced homotypic aggregation. However, a monoclonal antibody to CD44 induced a similar phenotype in activated lymphocytes. Induction of both homotypic in activated lymphocytes. Induction of both homotypic aggregation and the dendritic phenotype was abolished by preincubation with soluble intracellular adhesion molecule 1 (ICAM-1). Cytoskeletal inhibitors prevented the morphological changes in SPV-L7-activated lymphocytes. Preincubation with tyrosine kinase inhibitor, protein kinase C inhibitors, and inhibitors of new protein synthesis also prevented these morphological changes. These data suggest that discrete epitopes on LFA-1 alpha may be capable of inducing discrete signals either for homotypic aggregation or for a dendritic phenotype. As both LFA-1 and CD44 are involved in the migration of lymphocytes through high endothelial venules, these data could suggest that these molecules transduce signals resulting in cytoskeletal modification necessary for lymphocyte transmigration.
PUBLISHED
Keywords: Neurology; Immunology